Multi-functional muslim prayer attire (Telekung Solat) for disabled women / Fara Azeerin A Karim, Rosita Mohd Tajuddin - A Karim, Fara Azeerin; Mohd Tajuddin, Rosita (Universiti Teknologi MARA, 2020)
Prayer attire in the market is mostly designed for women with only one function and consists of two pieces’ cloth, which is the headcover and bottom piece. Many brands sell prayer attire, but they do not sell prayer attire that has specific designs for disabled women because they think it is not profitable. Unsuitable design for the disabled user especially on prayer attire and the existing product in the market does not fit and fulfil the attributes needed in terms of fabric and durability. Some issues need to be answered, which attributes need to be considered in designing prayer attire that will fulfil the multifunctional purposes and what are the needs required in multi-functional Muslim prayer attire for a wheelchair user. This research is aimed to identify the design attributes and to analyse the need to be considered in designing a Muslim prayer attire for wheelchair users focusing on Spinal cord injury. This study contributes to enhancing the existing prayer attire specifically for disabled women through multifunctional design attributes such as functionality, aesthetics and technical. The observation, survey and interview were used to obtain additional unknown or reliable information, authoritative opinions, serious and professional assessments of the research topic. This research found that the enhancement of the characteristics of multifunctional prayer attire for disabled women would improve the functional features in the design. The final product met the donning/ doffing, versatility, practicality and durability with the design projected to achieve the objective and also to educate the public on the importance of having a proper or suitable attire for disabled women which is multifunctional and comfortable, especially when performing prayers during religious activity.